2010
DOI: 10.3109/15622970903131597
|View full text |Cite
|
Sign up to set email alerts
|

Creatine transporter expression after antidepressant therapy in rats bred for learned helplessness

Abstract: In cells and tissues with a high demand of energy such as neurons the major pool of energy is supplied by phosphocreatine. The necessary supply with creatine is directly related to the expression level of the creatine transporter (CRT). To study possible interactions between this transporter and depressive like behavior we have used a congenitally learned helplessness (cLH) model. Because uptake via CRT is the only means to supply neurons with creatine, we hypothesized a rise in CRT expression following antide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The 5-HT system has been shown to play an important role in the acquisition of LH (Maier & Seligman 2016). Additionally, Lugenbiel et al (2010) found that rats bred for a congenital LH response (cLH) without induction have decreased Slc6a8 expression in Lack of creatine alters serotonin and affect 1 0 the hippocampus, but not the prefrontal cortex (Lugenbiel et al 2010). Both escitalopram and electroconvulsive shock administration are antidepressant treatments that attenuate LH-responses (Reed et al 2009;Sartorius et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT system has been shown to play an important role in the acquisition of LH (Maier & Seligman 2016). Additionally, Lugenbiel et al (2010) found that rats bred for a congenital LH response (cLH) without induction have decreased Slc6a8 expression in Lack of creatine alters serotonin and affect 1 0 the hippocampus, but not the prefrontal cortex (Lugenbiel et al 2010). Both escitalopram and electroconvulsive shock administration are antidepressant treatments that attenuate LH-responses (Reed et al 2009;Sartorius et al 2003).…”
Section: Discussionmentioning
confidence: 99%